El enriquecimiento sin causa en el contexto del contrato: a propósito del pago en exceso - Barchi Velaochaga, Luciano Juan Luis (2020)
Through this article the author intends to demonstrate how restitutionary claims originate in contracts, which are based on compulsory relations generated by heteronomous sources such as the arbitration agreement, deepening his analysis on excess payment.